Ballistic Impact Performance Of Wet Lamination Kega - Husain, Husri (2016)
The requirement for effective mobility mode, cost efficient, reliable protection and lightweight has become the main priority to the armor industries in their product design development phases such as hard body armor panel. As a result, rapid development in the new armor materials, coupled with more technological advancements has fueled growth in the industry. To support the interest of the armor industries for new materials particularly in hard body armor segment, the current research has taken an initiative to investigate the ballistic impact performance of a new variant of fiber metal laminate (FML) which consists of Kevlar 29, S-glass fibers and aluminum alloy 2024 T3 known as KeGa. As such, one of the issues that have caught the attention of the current study is that a newly FML-KeGa laminate must have reliable evaluation methods in order to justify its performance capability. In relation to this issue, the current research has employed both analytical and experimental approach as the evaluation method. The analytical approach based on macromechanics and wave dominated localized analysis were used to predict the safety index as fitness status and the ballistic impact performance of the KeGa laminate. For the experimental segment, the mechanical tests were employed to determine the basic lamina strength parameters and quasi-static linear elastic limit. After that, the gas gun impact tests were employed in order to quantify the ballistic impact performance of the KeGa laminate. Results showed that predicted ballistic impact performance of KeGa laminate is in good agreement with the experimental results. Furthermore, the results also signified that the geometrical size of the projectile as the main parameter for effective perforation mode while the plate thickness was significant for better plate resistance capability. In brief, the evaluation methods in this study provide a platform for research and development of KeGa and fiber metal laminate.